Bibliometric analysis of organizational cynicism - Wu, Hao; Subramaniam, Anusuiya; Rahamat, Syafiqah (Universiti Putra Malaysia, 2025)
Organizational cynicism represents a highly negative attitude held by employees towards their employing organizations. In recent years, research on organizational cynicism has been steadily increasing, often positioning it as a new paradigm in employer-employee relationships. Cynicism has significantly impacted organizations and societies in regions from the United States and Europe to Asia. However, bibliometric studies focusing on organizational cynicism are relatively scarce. Hence, this study systematically reviews the existing literature on organizational cynicism. This study conducted a comprehensive review of 163 articles from the Scopus database that pertain to organizational cynicism. Furthermore, utilizing bibliometric methods, the study analyzed publication trends, sources, co-authorship, citations, affiliated countries, organizations, funding sources, subject areas, and popular topics within the selected articles. This study systematically synthesizes the current literature on organizational cynicism and suggests emerging trends and potential directions for future research. This study holds substantial significance for guiding forthcoming inquiries in this domain.